Proceedings of the 2010 Symposium on Eye-Tracking Research &Amp; Applications - ETRA '10 2010
DOI: 10.1145/1743666.1743712
|View full text |Cite
|
Sign up to set email alerts
|

Towards task-independent person authentication using eye movement signals

Abstract: Figure 1: A Gaussian mixture model (GMM) with universal backround model (UBM).User-dependent models are adapted from the UBM and the recognition score is normalized using the UBM score. AbstractWe propose a person authentication system using eye movement signals. In security scenarios, eye-tracking has earlier been used for gaze-based password entry. A few authors have also used physical features of eye movement signals for authentication in a taskdependent scenario with matched training and test samples. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 8 publications
0
44
0
3
Order By: Relevance
“…However, there are several interesting experiments with different scenarios, including faces observation [25] or text reading [11]. There is also an attempt to perform identification without any information about a stimulus [18].…”
Section: Human Identification Using Eye Movementsmentioning
confidence: 99%
“…However, there are several interesting experiments with different scenarios, including faces observation [25] or text reading [11]. There is also an attempt to perform identification without any information about a stimulus [18].…”
Section: Human Identification Using Eye Movementsmentioning
confidence: 99%
“…Although they reported superior performance from keystroke-based biometric features, they also noted that eye movementbased features showed promising results, which warrant further investigation. Kinnunen, Sedlak, and Bednarik (2010) developed a task-dependent person identification system by applying Gaussian mixture models on feature vectors of short-term eye gaze direction. Their results suggested that there are task-dependent person-specific features in the eye movement, which may be useful in user authentication systems.…”
Section: Gaze Velocity As a Behavioral Biometricmentioning
confidence: 99%
“…For eye tracking data, proposed approaches include frequency analysis using the fast Fourier transform (Kinnunen et al, 2010), statistical analysis of velocity (Silver & Biggs, 2006), and morphological analysis based on graph-based representations (Rigas, Economou, & Fotopoulos, 2012) to name a few. In our previous studies (Yoon et al, 2014(Yoon et al, , 2015, we employed HMMs, a probabilistic model with promising performance for classifying independent temporal sequences.…”
Section: Classification Of Temporal Sequencesmentioning
confidence: 99%
“…More recently research has been done on the use of eye movement dynamics for biometric authentication [5,19,25,26]. Eye movement dynamics are similar to mouse dynamics except they track eye movement on a screen rather than the mouse.…”
Section: Eye Trackingmentioning
confidence: 99%